Agro-forestry for improvements of deforested mountain lands in Costa Rica, a pilot study - Heuveldop, J.; Chang, B. (CATIE, Turrialba (Costa Rica). Program of Natural Renewable Resources, 2014)
13 ref. Sum. (En)